2019
DOI: 10.1161/circheartfailure.118.005765
|View full text |Cite
|
Sign up to set email alerts
|

Targeted DNA Methylation Profiling of Human Cardiac Tissue Reveals Novel Epigenetic Traits and Gene Deregulation Across Different Heart Failure Patient Subtypes

Abstract: Targeted DNA methylation profiling of human cardiac tissue reveals novel epigenetic traits and gene deregulation across different Heart Failure patient sub-types Glezeva DNA methylation profiling of Heart Failure

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
70
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 77 publications
(77 citation statements)
references
References 17 publications
3
70
0
4
Order By: Relevance
“…Abnormal regulation of genes and/or proteins involved in sarcomere organization, expression of cardiac hormones and proto‐oncogenes, and extracellular matrix remodelling that directly influences cardiac function and structure has been described in numerous studies of DCM and heart failure . Moreover, it was recently suggested that epigenetic mechanisms play a pivotal role in the regulation of cardiac gene expression patterns during the progression of cardiac hypertrophy and failure . In the present study, nuclear DNA methylation in cardiomyocytes was found to correlate significantly with parameters of LV remodelling (LV dilatation and LV hypertrophy) and LV dysfunction.…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…Abnormal regulation of genes and/or proteins involved in sarcomere organization, expression of cardiac hormones and proto‐oncogenes, and extracellular matrix remodelling that directly influences cardiac function and structure has been described in numerous studies of DCM and heart failure . Moreover, it was recently suggested that epigenetic mechanisms play a pivotal role in the regulation of cardiac gene expression patterns during the progression of cardiac hypertrophy and failure . In the present study, nuclear DNA methylation in cardiomyocytes was found to correlate significantly with parameters of LV remodelling (LV dilatation and LV hypertrophy) and LV dysfunction.…”
Section: Discussionsupporting
confidence: 59%
“…Several studies have investigated genome‐wide DNA methylation in failing hearts. Movassagh et al reported that DNA methylation is altered in human failing hearts, and this was confirmed in subsequent studies . However, all of those studies assessed DNA methylation biochemically using immunoprecipitation chips, where DNA from not only cardiomyocytes but also other cell types within the myocardium was analysed without distinguishing among them.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…In the gene body (c), positive association has been demonstrated between increased methylation and transcriptional activation and elongation. Removal of 5MeC from the gene body therefore is associated with transcriptional repression aetiologies [40][41][42][43][44][45][46]. Further to the first reported alterations in DNA methylation in patients with end-stage HF [40,41], several major studies have specifically focussed on profiling DNA methylation changes in dilated cardiomyopathy (DCM) [42][43][44]47].…”
Section: Dna Methylation In Heart Failurementioning
confidence: 99%
“…In the context of ischaemic cardiomyopathy (ICM), differential DNA methylation has been linked with differences in gene expression compared to non-ischaemic cardiomyopathy, indicating that ICM correlates with relative hypermethylation of promoter-associated CGIs associated with repression of genes involved in oxidative metabolism [45]. , with significantly altered levels consistent with the direction of methylation identified in the particular HF patient sub-group [46]. There is also increasing evidence suggesting that 5hMeC generated by the action of TETs may play a functional role in remodelling processes in the heart [48,49].…”
Section: Dna Methylation In Heart Failurementioning
confidence: 99%